Inovasi Penilaian Hasil Belajar Model POT di Era Merdeka Belajar - Athoillah, Sukijan; Abu Bakar, M Yunus; Kholis, Nur (Universitas Islam Sultan Agung, 2024)
Assessment is an important thing in the curriculum. Because with the assessment, the learning carried out can be seen the results and follow-up. Assessment will always be developed in accordance with the curriculum. At present, the government has decided to implement an independent curriculum, starting from elementary school to tertiary level. An innovative assessment model can be a solution to the declining quality of education. This type of research is included in the systematic literature review. The results of this study are that the construction of the assessment model in the independent curriculum is very varied, ranging from project-based assessment, authentic assessment to summative research. All of this was done in order to form a Pancasila student profile.